EFFECT OF THE SUPPLIER SELECTION ON SUPPLY CHAIN EFFICIENCY IN COUNTY GOVERNMENT OF NANDI - Naomi Cherono, Naomi; Keitany, Pauline (International Journal of Supply Chain Management, 2021)
Purpose: The main purpose of this study was to evaluate the effect of supplier selection on the supply chain efficiencies in the county Government of Nandi. The study was guided by the following theories: transaction cost theory and the contingency theory. The study employed an explanatory survey which was cross-sectional in time dimension. Methodology: A proportionate stratified random sampling based on departmental section was utilized. The primary data collection procedure involved a survey where a self-administered questionnaire was used. With reference to content validity, the questionnaire was reviewed by a panel of experts before pilot testing was done. Once the data was cleaned, sorted and entered, it was analysed through the use of descriptive analysis (frequency distribution, means, standard deviation) with the data being presented in tabular and pictorial format. The inferential statistics (multiple regression), will be conducted at 95 per cent confidence level with significance levels of 0.05. The results were displayed using tables. Findings: The findings of the study indicated that supplier selection practices had positive and significant influence on supply chain efficiency, Kenya (Î² =0.114; p<0.05. The concluded that supplier selection is the predictor of supply chain efficiency of county government of Nandi. The study recommended that the county government of Nandi other organizations at large should show more commitment in SRM by having systems to monitor and appraise and evaluate performance at a strategic level. Unique contribution to theory, practice and policy: The study could be replicated in other industry sectors of the economy to build on the body of knowledge of supplier selection on performance of organizations.